Optimalisasi Potensi Sumber Daya Alam Desa Mbatakapidu melalui Program PKM Pembuatan Silase untuk Pakan Kambing - Samsul Arip Umbu Kaboka Jangi; Fekianus Kaka Mesa; Marco Gregorio Pareira; Agustina Bulu; Rindawani Rambu Tagu Hana; Ina Kaita Niwa; Samuel Erwin Djami; James Mandaha; Ninnoy Aquino Jefra Kote; Antotio Umbu Tagela; Sirappa, Iven Patu; Yessi Tamu Ina; Febyningsi Rambu Ladu Bana; Junaedin Wadu (Karya Nyata : Jurnal Pengabdian kepada Masyarakat, 2025)
Mbatakapidu Village has abundant natural resource potential, especially agricultural waste and local forages that have not been optimally utilized as animal feed. This Community Service. Program (PkM) aims to educate and empower the village community through counseling and training in making silage feed for goats, as a solution in providing quality feed in the area. The implementation method includes location surveys, making silage samples, technical training and direct assistance in the process of fermenting local forage into silage, and program evaluation carried out during March - May 2025. The results of the activities showed an increase in farmers' understanding and skills in processing local feed ingredients into silage, as well as growing awareness of the importance of feed technology in supporting sustainable local potential-based livestock productivity in Mbatakapidu Village.